N-Drop and Determiners in Native and Non-Native Spanish: More on the Role of Morphology in the Acquisition of Syntactic Knowledge - Liceras, Juana M.; Díaz, Lourdes; Mongeon, Caroline (Círculo de Lingüística Aplicada a la Comunicación, 2023)
In order to investigate whether the acquisition of N-drop (null nouns) is related to the acquisition of the agreement system of Spanish determiners this paper analyzes L1 longitudinal Spanish data from two children and L2 longitudinal data from two children learning Spanish in a naturalistic setting. Based on the results, it is argued that in L1, the acquisition of N-drop may be triggered by the feature ’word marker’ which constitutes the make-up of Spanish Nouns, Adjectives and Determiners (Harris 1991, Berstein 1993). However, in the case of L2 acquisition, projecting the abstract ‘word marker’ feature of the Spanish DP the morphology of the Spanish determiner may not be a condition for the productive use of Null Nouns. We base this conclusion on the following pieces of evidence: (1) Monosyllabic place-holders (non-tonic vowels which appear before referential categories) occur in child L1 Spanish, which leads us to propose that these items play a role in the projection of the abstract [+word marker] syntactic feature in L1 Spanish; (2) Monosyllabic place-holders do not occur in child non-native Spanish, which leads us to propose that L2 acquires’ sophisticated phonological systems may prevent them from dissecting the incoming input data (using a ‘bottom up’ processing strategy) which leads to the projection of abstract features; (3) In L1 acquisition non-adult null determiners cease to occur when N-drop becomes productive. This is not the case on L2 acquisition, which again leads us to propose that L2 acquires do not rely on the ‘bottom up’ strategy to deal with input data; (4) In L1 acquisition gender mismatches cease to occur when N-drop becomes productive. In the case of L2 acquisition there is not correlation between productive use of N-drop and the disappearance of gender mismatches. Given the fact that the morphological realization of word markers and gender markers is difficult to tease apart in Spanish, these results provide further evidence that L1 learners make indirect use of morphological markers (via phonological dissection) to project abstract syntactic features.